2005
DOI: 10.1681/asn.2004121039
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Comparison of Full and Partial Anemia Correction in Incident Hemodialysis Patients without Symptomatic Heart Disease

Abstract: It is unclear whether physiologic hemoglobin targets lead to cardiac benefit in incident hemodialysis patients without symptomatic heart disease and left ventricular dilation. In this randomized, double-blind study, lower (9.5 to 11.5 g/dl) and higher (13.5 to 14.5 g/dl) hemoglobin targets were generated with epoetin ␣ over 24 wk and maintained for an additional 72 wk. Major eligibility criteria included recent hemodialysis initiation and absence of symptomatic cardiac disease and left ventricular dilation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
302
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(325 citation statements)
references
References 30 publications
13
302
1
7
Order By: Relevance
“…Anemia is frequently encountered in chronic kidney disease (CKD) and is associated with cardiovascular outcomes in patients with CKD 1. Correcting anemia usually requires erythropoiesis‐stimulating agents (ESAs).…”
Section: Introductionmentioning
confidence: 99%
“…Anemia is frequently encountered in chronic kidney disease (CKD) and is associated with cardiovascular outcomes in patients with CKD 1. Correcting anemia usually requires erythropoiesis‐stimulating agents (ESAs).…”
Section: Introductionmentioning
confidence: 99%
“…8 However, it is less clear that increases in hemoglobin beyond current targets (generally 11 to 12-13 g/dL) will result in any material improvement in health-related quality of life. 9 Moreover, there is some evidence to suggest that strategies aimed to normalize hemoglobin concentrations could be harmful. 10,11 Therefore, other potential strategies to optimize health-related quality of life in the ESRD population must be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the correction of anemia in patients with CKD improves the quality of life and exercise tolerance while reducing the need for transfusion. 31 In 2000, a panel of the Kidney Disease Outcomes Quality Initiative of the National Kidney Foundation recommended that the target level of Hgb should be 11.0 to 12.0 g per deciliter in patients with CKD, whether or not they were receiving dialysis. 32 A recent update of guidelines regarding anemia in such patients expanded the target range to 11.0 to 13.0 g per deciliter.…”
Section: Discussionmentioning
confidence: 99%